SISTEM MONITORING DAN PENGENDALIAN PENYIRAMAN TAMANAMAN OTOMATIS BERBASIS INTERNET OF THINGS MENGGUNAKAN ESP32 DAN DELPHI - Indra Maulana; Danu Tirta; Dhimas Hamzah; Naila Sapitri; Fericha Chaerani; Pipin Ervina (TechNova: Journal of Informatics and Information Systems (TJIIS), 2026)
Manual plant watering can cause delayed irrigation, water waste, and difficulty monitoring plant conditions remotely. This study aims to design and implement an Internet of Things (IoT)-based automatic plant watering system using ESP32 and a Delphi desktop application for monitoring and control via WiFi. The system uses a Soil Moisture sensor to measure soil moisture and a DHT11 sensor to monitor air temperature and humidity, with data exchanged through HTTP using JSON format. The Prototype method was applied through requirement analysis, system design, prototyping, implementation, testing, and evaluation. The system provides Auto mode to control the pump based on soil moisture levels and Manual mode to control the pump through the Delphi application. Testing results show that all modules function as designed and the system enables real-time monitoring and control without requiring a data cable.